FINANCE OF INSURANCE ORGANIZATION - Tugizova Malika Sokhib kizi (Zeta Repository, 2023)
Different levels of insurance tariff in each life insurance contract or calculate and set the rate of return independently for each contract. Profitability standards for life insurance classes should be strictly defined, and changes to its tariff rates should be made in agreement with the authorized body of the state. In insurance organizations, the basic income and expense account differs in its specificity. The total amount of money received in the account as a result of carrying out insurance, engaging in other activities not prohibited by law is considered as its income.